Is blood lymphocyte count a prognostic biomarker in Staphylococcus aureus bacteremia?. (30th May 2022) - Blot, Mathieu; Zeggay, Abdeljalil; Aho-Glele, Ludwig-Serge; Laborde, Caroline; Le Moing, Vincent; Chirouze, Catherine; Bouiller, Kevin; Piroth, Lionel
Abstract : Lymphopenia is common in patients with sepsis and associated with mortality. Immune-stimulatory therapies likely to restore T-cells count and function are under investigation in sepsis. Our study aimed to assess whether lymphopenia is a reliable prognostic biomarker in Staphylococcus aureus bacteremia. We conducted an ancillary study of the prospective VIRSTA Study including 574 patients with S. aureus bacteremia in two tertiary care centers. Neither lymphocyte count at the onset nor lymphocyte change during the first 4 days was associated with 12-week mortality. These results highlight the importance of characterizing the immune profile of patients with sepsis according to the cause before investigating immunostimulatory therapies to restore lymphocyte proliferation and function.